Kinesiological Rehabilitation in a Young Adult with Biceps Femoralis Arteriovenous Malformation: A Case Study - Giulia Di Martino; Carlo della Valle; Marco Centorbi; Paola Bovolenta; Giovanni Fiorilli; Giuseppe Calcagno; Alessandra di Cagno; Enzo Iuliano (Journal of Functional Morphology and Kinesiology)
Background/Objectives: This case study involved a 24-year-old male with an arteriovenous malformation localized in the long head of the right biceps femoris muscle, with an anterior cruciate ligament injury. The aim was to assess the effects of a five-week kinesiological protocol, which included global postural re-education and strengthening exercises focused on knee stabilization. Methods: The effectiveness of the therapeutic intervention was evaluated using Gait Analysis, clinical examination, and the SF-36 questionnaire to assess the patient’s quality of life. Results: The study revealed significant postural improvements, including the restoration of the spine’s physiological curves, with kyphosis angles measuring 44.7° in indifferent orthostasis and 41.7° in self-corrected standing; and lumbar lordosis measuring 32.8° in indifferent orthostasis and 41.9° in self-corrected standing. Additionally, there was a restoration of the correct knee, hip, and ankle angles, along with a shift in the principal axis of the center of pressure from 7.6° pre-intervention to 12.9° post-intervention. The patient’s perception of physical efficiency also improved, increasing from 60% to 75% over the treatment period. Conclusions: The effectiveness of the kinesiological treatment was confirmed by the improvement in gait stability and overall strengthening. The patient’s active involvement in the treatment process enhanced his confidence in its success, ensuring adherence to the protocols.